10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Natalizumab is a highly effective therapy but may impair central nervous system (CNS) immune surveillance, leading to rare opportunistic infections. We report a fatal case of cerebral toxoplasmosis under natalizumab. A 61-year-old man with stable multiple sclerosis (MS) developed acute hemiparesis on natalizumab therapy. Magnetic resonance imaging (MRI) showed multiple ring-enhancing lesions. Brain biopsy and polymerase chain reaction (PCR) confirmed reactivated Toxoplasma gondii. A low-risk IgG κ monoclonal gammopathy of undetermined significance (MGUS) was identified. Despite antiparasitic therapy, the patient developed coma and died. Natalizumab-induced CNS immune compartmentalization, combined with subtle MGUS-related immune dysfunction and immunosenescence, may have facilitated intracerebral reactivation. Vigilance for opportunistic infections may be warranted in older patients with hematologic comorbidities receiving natalizumab.